Does Nasal Surgery Affect Voice Outcomes? A Systematic Review with Meta-Analyses. (December 2020) - Xiao, Christopher C; Luetzenberg, Friederike S.; Jiang, Nancy; Liang, Jonathan
Objectives: Changes in airflow dynamics after nasal surgery may have implications on voice quality. Multiple studies have evaluated the impact of nasal surgery on voice using heterogeneous outcome measures. We aim to systematically review the impact of nasal surgery on voice quality. Methods: Our study design was a systematic review with meta-analyses. A literature search of PubMed, Ovid, Cochrane from 1997 to 2017 was performed. Inclusion criteria included English language studies containing original data on nasal surgery and voice. Two investigators independently reviewed all manuscripts and performed a comprehensive quality assessment. Meta-analysis was completed on quantitative voice measurements. Results: Of 463 identified, 19 studies with 692 patients fulfilled eligibility. Nasal surgeries performed included endoscopic sinus surgery (11/20), septoplasty (11/20), rhinoplasty (2/20), and turbinate reduction (2/20). Voice outcomes measured included nasalance (8/20), fundamental frequency (11/20), jitter (10/20), shimmer (10/20), harmonic to noise ratio (HRN) (8/20), formants (5/20), and voice handicap index (VHI) (4/20). Voice examinations were assessed preoperatively and 1 to 30 months postoperatively. Meta-analysis revealed statistically significant changes in nasalance, ( P < .01) 1 month postoperatively; there was no significant difference in nasalance at 6 months postoperatively. All other variables analyzed revealed no statistically significant differences. Five of nine studies showed majority of patients did not notice subjective change in voice after surgery, but with high heterogeneity of measurements. Conclusions: There may be a short-term increase in nasalance that resolves at longer follow-up, but there seem to be no other objective changes in voice. There may be subjective changes after surgery, but require further study to evaluate.